The Australian Institute of Sport (AIS) framework for rebooting sport in a COVID-19 Environment. Executive summary and appendixes (Australian Institute of Sport, 2020)
Sport makes an important contribution to the physical, psychological and emotional well-being of Australians. The economic contribution of sport is equivalent to 2-3% of Gross Domestic Product (GDP). The COVID-19 pandemic has had devastating effects on communities globally, leading to significant restrictions on all sectors of society, including sport. Resumption of sport can significantly contribute to the re-establishment of normality in Australian society.The Australian Institute of Sport (AIS), in consultation with sport partners (National Institute Network (NIN) Directors, NIN Chief Medical Officers (CMOs), National Sporting Organisation (NSO) Presidents, NSO Performance Directors and NSO CMOs), has developed a framework to inform the resumption of sport. National Principles for Resumption of Sport were used as a guide in the development of `the AIS Framework for Rebooting Sport in a COVID-19 Environment` (the AIS Framework); and based on current best evidence, and guidelines from the Australian Federal Government, extrapolated into the sporting context by specialists in sport and exercise medicine, infectious diseases and public health. The principles outlined in this document apply equally to high performance/professional level, community competitive and individual passive (non-contact) sport. The AIS Framework is a timely tool for `how` reintroduction of sport activity will occur in a cautious and methodical manner, to optimise athlete and community safety. Decisions regarding the timing of resumption of sporting activity (the `when`) must be made in close consultation with Federal, State/Territory and/or Local Public Health Authorities. The priority at all times must be to preserve public health, minimising the risk of community transmission.